2012
DOI: 10.1038/ncb2603
|View full text |Cite
|
Sign up to set email alerts
|

Nanog-dependent feedback loops regulate murine embryonic stem cell heterogeneity

Abstract: A number of key regulators of mouse embryonic stem (ES) cell identity, including the transcription factor Nanog, show strong expression fluctuations at the single cell level. The molecular basis for these fluctuations is unknown. Here we used a genetic complementation strategy to investigate expression changes during transient periods of Nanog downregulation. Employing an integrated approach, that includes high-throughput single cell transcriptional profiling and mathematical modelling, we found that early mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
175
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 142 publications
(186 citation statements)
references
References 56 publications
10
175
1
Order By: Relevance
“…It has been suggested that different topologies of pluripotent gene regulatory networks maintain the heterogeneous molecular states characteristic of individual PSCs 60. Recently, different studies have addressed this important question by integrating single cell expression and perturbation data for identifying the underlying PGRNs 4, 16, 22, 61, which are involved in the stabilization of the pluripotent state and lineage commitment 62, 63. In most of these studies, topological analyses of PGRNs have identified feed forward loops (FFLs) linked to regulation of the balance between self‐renewal and differentiation.…”
Section: Subpopulation‐specific Gene Regulatory Network Can Be Infermentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that different topologies of pluripotent gene regulatory networks maintain the heterogeneous molecular states characteristic of individual PSCs 60. Recently, different studies have addressed this important question by integrating single cell expression and perturbation data for identifying the underlying PGRNs 4, 16, 22, 61, which are involved in the stabilization of the pluripotent state and lineage commitment 62, 63. In most of these studies, topological analyses of PGRNs have identified feed forward loops (FFLs) linked to regulation of the balance between self‐renewal and differentiation.…”
Section: Subpopulation‐specific Gene Regulatory Network Can Be Infermentioning
confidence: 99%
“…activation and inhibition, respectively – have great information processing potential, allowing the generation of alternative output solutions. The feedback structure of the PGRNs have been reported to be partially destroyed, with main variations in the loop between Nanog and other pluripotency factors, leading to a transient activation of different motifs that trigger differentiation 16. Incoherent FFLs have been inferred in mESCs subpopulations linking Oct4 and Nanog with their gene targets, suggesting an antagonistic interaction between these TFs for the regulation of pluripotency and self‐renewal 4.…”
Section: Subpopulation‐specific Gene Regulatory Network Can Be Infermentioning
confidence: 99%
See 3 more Smart Citations